GeospaceLAB: Python package for managing and visualizing data in space physics - Cai, Lei; Aikio, Anita; Kullen, Anita; Deng, Yue; Zhang, Yongliang; Zhang, Shun-Rong; Virtanen, Ilkka; Vanhamäki, Heikki (Frontiers in Astronomy and Space Sciences, 2022)
In the space physics community, processing and combining observational and modeling data from various sources is a demanding task, because they often have different formats and use different coordinate systems. The Python package GeospaceLAB has been developed to provide a unified, standardized framework to process data. The package is composed of six core modules, including DataHub as the data manager, Visualization for generating publication quality figures, Express for higher-level interfaces of DataHub and Visualization, SpaceCoordinateSystem for coordinate system transformations, Toolbox for various utilities, and Configuration for preferences. The core modules form a standardized framework for downloading, storing, post-processing, and visualizing data in space physics. The object-oriented design makes the core modules of GeospaceLAB easy to modify and extend. So far, GeospaceLAB can process more than twenty kinds of data products from nine databases, and the number will increase in the future. Data sources include, e.g., measurements by EISCAT incoherent scatter radars, DMSP, SWARM, and Grace satellites, OMNI solar wind data, and GITM simulations. In addition, the package provides an interface for the users to add their own data products. Hence, researchers can easily collect, combine, and view multiple kinds of data for their work using GeospaceLAB. Combining data from different sources will lead to a better understanding of the physics of the studied phenomena and may lead to new discoveries. GeospaceLAB is open-source software, which is hosted on GitHub. We welcome everyone in the community to contribute to its future development.